Tumor cell metabolic reprogramming and hypoxic immunosuppression: driving carcinogenesis to metastatic colonization - Katopodi, Theodora; Petanidis, Savvas; Anestakis, Doxakis; Charalampidis, Charalampos; Chatziprodromidou, Ioanna; Floros, George; Eskitzis, Panagiotis; Zarogoulidis, Paul; Koulouris, Charilaos; Sevva, Christina; Papadopoulos, Konstantinos; Dagher, Marios; et al. (Frontiers in Immunology, 2024)
A significant factor in the antitumor immune response is the increased metabolic reprogramming of immunological and malignant cells. Increasing data points to the fact that cancer metabolism affects not just cancer signaling, which is essential for maintaining carcinogenesis and survival, but also the expression of immune cells and immune-related factors such as lactate, PGE2, arginine, IDO, which regulate the antitumor immune signaling mechanism. In reality, this energetic interaction between the immune system and the tumor results in metabolic competition in the tumor ecosystem, limiting the amount of nutrients available and causing microenvironmental acidosis, which impairs the ability of immune cells to operate. More intriguingly, different types of immune cells use metabolic reprogramming to keep the body and self in a state of homeostasis. The process of immune cell proliferation, differentiation, and performance of effector functions, which is crucial to the immune response, are currently being linked to metabolic reprogramming. Here, we cover the regulation of the antitumor immune response by metabolic reprogramming in cancer cells and immune cells as well as potential strategies for metabolic pathway targeting in the context of anticancer immunotherapy. We also discuss prospective immunotherapymetabolic intervention combinations that might be utilized to maximize the effectiveness of current immunotherapy regimes.